2012
DOI: 10.3928/01477447-20111122-34
|View full text |Cite
|
Sign up to set email alerts
|

Femoral Neck Fracture Following Hardware Removal

Abstract: It is uncommon for femoral neck fractures to occur after proximal femoral hardware removal because age, osteoporosis, and technical error are often noted as the causes for this type of fracture. However, excessive alcohol consumption and failure to comply with protected weight bearing for 6 weeks increases the risk of femoral neck fractures.This article describes a case of a 57-year-old man with a high-energy ipsilateral inter-trochanteric hip fracture, comminuted distal third femoral shaft fracture, and displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…Information about indication and complications for IR in healed proximal femur fractures can be seen as sparse in the current literature [1,2,[11][12][13][14]. When comparing the MIR with the NMIR subgroup, a statistical significant finding according to complications with 11.46% versus 28% was observed.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Information about indication and complications for IR in healed proximal femur fractures can be seen as sparse in the current literature [1,2,[11][12][13][14]. When comparing the MIR with the NMIR subgroup, a statistical significant finding according to complications with 11.46% versus 28% was observed.…”
Section: Discussionmentioning
confidence: 66%
“…Indications and time interval for hardware removal in this special selected patient group is controversial in the literature [2,10,11,[13][14][15][16][17][18] neck fracture in the presence of fixation for intertrochanteric fractures, reports of ipsilateral femoral neck fractures after hardware removal from healed fractures are rare in the previous literature [9][10][11][12][13]18,19]. Secondary fractures after implant removal have a range from 27 to 44% in proximal femoral fractures [2,19], while other complications associated with IR are mechanical failure, pain and infection [12,14].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…There is little information about the incidence of this type of fracture in the literature, whereas some retrospective studies reported a relatively high refracture rate after the plate removal from healed fractures. 10 As FNFs in the presence of fixation for an intertrochanteric fracture have been reported by several authors, it is possible that FNFs were present before hardware removal. The FNF after hardware removal from a healed intertrochanteric fracture has been reported incidentally in the literature.…”
Section: Discussionmentioning
confidence: 96%
“…The problem is further compounded when the initial screw was inserted percutaneously or via a minimally-invasive (MIS) technique. Multiple failed attempts at buried screw removal cause undue skin and soft tissue trauma from repeated manipulation and require more extensive incisions and bone loss, all of which could have obvious impact on the risk of wound complications, hardware breakage, iatrogenic fractures [ 10 , 11 ] and cosmesis [ 12 - 15 ].…”
Section: Introductionmentioning
confidence: 99%